Calorimetric measurement of the standard enthalpy of formation of ZnSb at 298 K. (September 2017) - Benigni, P.; Berche, A.; Pothin, R.; Adenot, A.; Mikaelian, G.; Ayral, R.M.; Jund, P.; Rogez, J.
Abstract: After a critical review of the literature data on the standard enthalpy of formation of ZnSb, discrepancies between various experimental studies are highlighted. Moreover, experimental values disagree with values calculated by ab initio methods. As many of the experimental methods used suffer from some serious drawbacks, a new determination of the standard enthalpy of formation of ZnSb by an alternative calorimetric method, drop solution calorimetry in liquid tin, has been performed. Two different synthesis methods have been used to obtain a pure ZnSb phase and drop solution experiments were performed at 665 and at 974 K. The standard enthalpy of formation values derived from these experiments are − 6.1±2.5 kJ mol of atoms −1 for the ZnSb sample prepared by ball milling and − 7.9±0.4 kJ mol of atoms −1 for the ZnSb sample prepared by melting. These results are discussed and compared to literature data.